Accommodation Business Competition in Bali: Competitive Strategy for Star Hotel in Sanur - Wijaya, Agung Rendra; Bendesa, I Komang Gde; Wiranatha, Agung Suryawan (E-Journal of Tourism; Volume 8 Number 1 (March 2021)DO - 10.24922/eot.v8i1.71446, 2021)
Sanur area, with Kuta, are two of Bali’s pioneering tourism areas. Most of the star hotels in Bali are located in these two areas. This paper is intended to determine the conditions of competition in the accommodation business in Bali Province, especially competition between star hotels in Sanur Tourism Area, as well as to elaborate the competitive strategy to maintain business sustainability. Through primary data collection by interviewing 8 managers and 14 employees at 3-star hotels in the Sanur area in 2018, the Delphi method was used to find a viable competitive strategy to choose from. The results of the SWOT analysis showed that the hotel location near the beach, and the incompleteness of MICE facilities were the main strength and weakness respectively. On the other hand, Bali’s popularity as a world-class destination and unfair price competition were the main opportunity and threat facing the accommodation business in Sanur respectively. This research found the competitive strategy to use is to intensify the use of Information Technology in the form of digitizing accommodation businesses.